Complex formation and internal proton-transfer of hydroxyl-hydrogen anion complexes at low temperature. (July 2015) - Hauser, Daniel; Lakhmanskaya, Olga; Lee, Seunghyun; Roučka, Štěpán; Wester, Roland
Abstract We have studied the three-body complex formation rate of the hydroxyl anion with molecular hydrogen at low temperatures. The formed cluster is found to quickly undergo internal proton transfer to a hydrogen anion–water complex. This is probed by photodetachment spectroscopy, which clearly distinguishes the two isomeric structures. The product cluster is the only isomer found to be stably formed at the temperature and densities employed in the experiment. The cluster then binds an additional hydrogen molecule by a second three-body collision, which appears at a rate comparable to the first formation process. This is followed by a rapid growth to larger clusters.